Rancang Bangun Aplikasi Pelayanan Pada Restoran Berbasis Mobile Android - Ramadhanis, Puspayati; Arifin, Mochammad; Jusak, Jusak (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Malioboro Kartini Surabaya Restaurant process experienced problem in a matter of service time which is slow because the process of finding an empty table done by direct combing each room, order recorded in three sheets to be given to the checker, bartender andÂ  customer directly, and also reservation list is not arranged well so the waitress have difficulty in obtaining information on the table-booking. Restaurant need a system to help waitress in addressing difficulties on servingÂ  customer. Therefore made Android Mobile Based Restaurant Service Application. Waitress operating Android tablet to show each room table map. Waitress marking a table to do the process of recording the order menu. Order list will automatically appear on checker desktop application to be controlled. After customer pay the bill, red mark on table will disappear. Stored reservation data will automatically appear on table map with purple mark. Serving application can help waitress to provide customer an empty table information immediately, sending order list automatically to checker, showing information about reserved table so waithress can immediately prepared the table